Is Pathology a Basic Science Subject? - Haque, Anwar Ul (International Journal of Pathology, 2018)
It is shocking to see that pathology is not includedamong Clinical Science Subjects by Pakistan Medical& Dental Council (PMDC). It’s included amongBasic Sciences while Radiology is considered a clinicalsubject by PMDC!